Vacuolar protein sorting mechanisms in plants. (11th January 2013) - Xiang, Li; Etxeberria, Ed; Van, Wim
<x xml:space="preserve">Abstract</x> Plant vacuoles are unique, multifunctional organelles among eukaryotes. Considerable new insights in plant vacuolar protein sorting have been obtained recently. The basic machinery of protein export from the endoplasmic reticulum to the Golgi and the classical route to the lytic vacuole and the protein storage vacuole shows many similarities to vacuolar/lysosomal sorting in other eukaryotes. However, as a result of its unique functions in plant defence and as a storage compartment, some plant‐specific entities and sorting determinants appear to exist. The alternative post‐Golgi route, as found in animals and yeast, probably exists in plants as well. Likely, adaptor protein complex 3 fulfils a central role in this route. A Golgi‐independent route involving plant‐specific endoplasmic reticulum bodies appears to provide sedentary organisms such as plants with extra flexibility to cope with changing environmental conditions.